2011
DOI: 10.1161/strokeaha.110.604983
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Level Measurement Improves Mortality Prediction When Added to the Spontaneous Intracerebral Hemorrhage Score

Abstract: Background and Purpose-Hyperglycemia and inflammation are involved in the progression of spontaneous intracerebral hemorrhage (sICH)-induced brain injury, but their role in predicting clinical outcome is not clear. We sought to determine whether elevation of white blood cell count (WBC), C-reactive protein (CRP), and blood glucose (BG) concentration at presentation prognosticate poor outcome in sICH patients. Methods-Between November 1, 2005 and October 31, 2009, 210 patients admitted to 2 intensive care units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 30 publications
2
61
0
Order By: Relevance
“…A large number of observational studies (21 studies, total number of patients=12 145, Table S6)2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32 have examined the association between glucose with ICH outcome with the majority (15 studies, total n=11 161) defining hyperglycemia on the basis of single glucose measurement. One notable study was the post hoc analysis of the Intensive Blood Pressure Reduction in Acute Cerebral Hemorrhage Trial (INTERACT) II study (n=2653) 30.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of observational studies (21 studies, total number of patients=12 145, Table S6)2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32 have examined the association between glucose with ICH outcome with the majority (15 studies, total n=11 161) defining hyperglycemia on the basis of single glucose measurement. One notable study was the post hoc analysis of the Intensive Blood Pressure Reduction in Acute Cerebral Hemorrhage Trial (INTERACT) II study (n=2653) 30.…”
Section: Discussionmentioning
confidence: 99%
“…In a large ICH cohort, elevated blood C-reactive protein (CRP) was independently associated with increased 30-day mortality after ICH and even added an 8% improvement to the accuracy of the Hemphill score model [66]. …”
Section: Selection Of Blood Biomarkers In Ichmentioning
confidence: 99%
“…Previous studies have identified several clinical [1,2,3,4,5,6], radiographic [4,7] and laboratory variables [8,9,10] that are associated with mortality after ICH.…”
Section: Introductionmentioning
confidence: 99%